Clarification of the Acoustic Characteristics of Velopharyngeal Insufficiency by Acoustic Simulation Using the Boundary Element Method: A Pilot Study - Mami Shiraishi; Katsuaki Mishima; Masahiro Takekawa; Masaaki Mori; Hirotsugu Umeda (Acoustics, 2025)
A model of the vocal tract that mimicked velopharyngeal insufficiency was created, and acoustic analysis was performed using the boundary element method to clarify the acoustic characteristics of velopharyngeal insufficiency. The participants were six healthy adults. Computed tomography (CT) images were taken from the frontal sinus to the glottis during phonation of the Japanese vowels /i/ and /u/, and models of the vocal tracts were created from the CT data. To recreate velopharyngeal insufficiency, coupling of the nasopharynx was carried out in vocal tract models with no nasopharyngeal coupling, and the coupling site was enlarged in models with nasopharyngeal coupling. The vocal tract models were extended virtually for 12 cm in a cylindrical shape to represent the region from the lower part of the glottis to the tracheal bifurcation. The Kirchhoff–Helmholtz integral equation was used for the wave equation, and the boundary element method was used for discretization. Frequency response curves from 1 to 3000 Hz were calculated by applying the boundary element method. The curves showed the appearance of a pole–zero pair around 500 Hz, increased intensity around 250 Hz, decreased intensity around 500 Hz, decreased intensities of the first and second formants (F1 and F2), and a lower frequency of F2. Of these findings, increased intensity around 250 Hz, decreased intensity around 500 Hz, decreased intensities of F1 and F2, and lower frequency of F2 agree with the previously reported acoustic characteristics of hypernasality.